Geoprocessing applied to cartographic mapping of the city of União dos Palmares - AL - Oliveira, Bruno Rodrigues de; Antônio, Gabriela Branquinho (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper’s objective is to develop a cartographic base of União dos Palmares – AL City using Remote Sensing technologies to obtain data and a Geographic Information System – GIS, which allows collect, store, process and analyze large amounts of spatially referenced data from different sources in the same database. The GIS allows data to be linked, correlated and interpreted in the same virtual environment, thus obtaining products with quality and precision. This way were elaborated thematic maps of the hipsometria, slope, hydrology, vegetation, geology, pedology, geomorphology, irrigated culture capability based on the most updated data available. The objective was to evaluate public policies of urban planning, implementation of civil works and delimitation of hazardous areas by slip / floods providing most updated cartographic bases.